Employment Effect of Minimum Wage Increase - Kyungsoo Choi (Korea Development Institute (KDI), 2018)
The objective of a minimum wage increase is to improve the quality of low-wage jobs and to narrow wage gaps. The sharp minimum wage increase in 2018 has so far produced no significant declines in employment. However, if drastic increases continue in the next two years, the level of the minimum wage as a ratio to the median wage will exceed those in other advanced economies and employment growth will likely exhibit a large drop distorting the wage structure. Thus, an adjustment in the pace of minimum wage increases is required. - The purpose of theminimum wage increase isto guarantee the wagelevel of the low-paid, thenumber of which isgrowing as personalservice jobs increase. - The share of below-minimum wage workers was 7.6% in the MOEL's 2016 Wage Survey and 13.4% in Statistics Korea's 2017 Economically Active Population Survey. - Other than cutting employment, there are several options available to employers to respond to the minimum wage increase such as raising prices, shortening working hours, reducing employee benefits/allowances and strengthening labor intensity. - Unlike individual companies facing their wage increase, a rise in the legislated minimum wage applies to the overall economy, meaning that companies can adjust prices to spread out the impact. - The majority of job loss resulting from an increase in the minimum wage is observed in the manufacturing industry while the impact has been weak in services sectors. - The higher the minimum-to-median wage ratio, the smaller the impact from the minimum wage increase. In 2016, the ratio marked 35% for the US and 50% for Korea. - Hungary raised the minimum wage by 60% in 2000-2004 in real terms, commensurate with Korea's planned increase. The employment of wage workers retreated by approx. 2%. - If Hungary's estimate is applied, Korea is estimated to see a decrease of 84,000 in employment after the minimum wage increase in 2018. If the US' is applied, the decrease is estimated to be 36,000. As such, Korea's decline in employment is expected at between 36,000 and 84,000. - Growth in employment in April 2018 was smaller by 180,000 than January, but the decrease was more influenced by January's high growth, slowing population growth and manufacturing restructuring than by the minimum wage increase. - If the sharp increase in the minimum wage is repeated in the next two years, the share of minimum wage workers will rise and impact on employment will grow. - The employment effect of the minimum wage increase is estimated to be a decrease of 96,000 in 2019 and 144,000 in 2020, when the effects of the job stabilization fund is not considered. - France experienced other side effects with a very high minimum wage such as disruption of the wage order, etc. Accordingly, France ceased additional minimum wage hikes after reaching 60% of the median. - Germany adjusts its minimum wage level every two years, as evaluation of the impact of the hike takes two years. - Measures must be sought to minimize the unexpected negative impact while efforts are made to maximize the positive.
Keywords: 330